Medical nutrition therapy and home monitoring in type 2 diabetes mellitus patient with metabolic syndrome and history of diabetic ketoacidosis - Anak Agung Eka Widya Saraswati; Yohannessa Wulandari; Lily Indriani Octovia (World Nutrition Journal, 2022)
Obesity, one of the risk factors for mtype 2 diabetes mellitus (T2DM), is known to cause low-grade inflammation and increase T2DM morbidity. Obesity and T2DM also lead to other comorbidities, such as metabolic syndrome. The provision of medical nutrition therapy accompanied with routine home monitoring could improve glycemic control and achieve therapeutic targets, simultaneously.